2021
DOI: 10.1177/13524585211018349
|View full text |Cite
|
Sign up to set email alerts
|

Associations of social network structure with cognition and amygdala volume in multiple sclerosis: An exploratory investigation

Abstract: Background: Humans are inherently social, biologically programmed to connect with others. Social connections are known to impact mental and physical health. Objective: The aim of this study was to test whether social network structure is linked to cognition, mood, fatigue, and regional brain volumes in persons with multiple sclerosis (MS). Methods: A questionnaire quantifying individual-level social network structure (size, density, effective size, and constraint), a comprehensive battery of neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Seventeen studies were identified that investigated associations between structural brain measures and depression (Table 1) [29, 47, 96–102, 132135, 137, 138, 140, 141]. 10/17 studies did not find any associations (Table 1) [98, 99, 102, 118, 132134, 138, 140, 141] and 7/17 reported significant associations (Tables 1 and 2) between structural measures and depression severity [29, 47, 96, 97, 100, 135, 137]. Of note, seven of these 17 studies investigated WML measures [29, 96, 98, 99, 101, 102, 141], but only three observed associations between depression and lesion load [29, 96, 137].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies were identified that investigated associations between structural brain measures and depression (Table 1) [29, 47, 96–102, 132135, 137, 138, 140, 141]. 10/17 studies did not find any associations (Table 1) [98, 99, 102, 118, 132134, 138, 140, 141] and 7/17 reported significant associations (Tables 1 and 2) between structural measures and depression severity [29, 47, 96, 97, 100, 135, 137]. Of note, seven of these 17 studies investigated WML measures [29, 96, 98, 99, 101, 102, 141], but only three observed associations between depression and lesion load [29, 96, 137].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast however, four studies reported an absence of associations between thalamic atrophy and fatigue scores [112, 116, 120, 125]. Similarly, the absence of association was reported between fatigue and basal ganglia volume [108], the limbic system [112], and amygdala volume [140].…”
Section: Resultsmentioning
confidence: 99%
“…The group-based format leverages social support as a therapeutic tool and maximizes potential benefits, as social isolation is a risk factor for anxiety in MS 10 and smaller and more tightly bound social network structure is related to worse physical and cognitive function in PwMS. 19,20 Additionally, professionally moderated support groups provide benefits on three levels: (1) the group leader is a licensed psychologist with extensive clinical experience; (2) group members are supported by each other; (3) group members turn their focus to helping each other, which is therapeutic. 21,22 A control comparison group (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Adverse personal social networks are associated with social isolation and loneliness, which may have direct biological effects by altering inflammation, recovery from injury, and resilience against neurodegeneration. [10][11][12][13] Personal social network structures (e.g., larger network size, more diffuse connections among network members) are associated with language function and regional brain volume in pwMS. 14 Examining personal social network structure (e.g., network size, density) and composition (e.g., demographics, health behaviors of the network members) in relation to disability accumulation in MS could potentially inform novel interventions.…”
Section: Introductionmentioning
confidence: 99%
“…8, 9 Adverse personal social networks are associated with social isolation and loneliness, which may have direct biological effects by altering inflammation, recovery from injury, and resilience against neurodegeneration. 10-13 Personal social network structures ( e . g ., larger network size, more diffuse connections among network members) are associated with language function and regional brain volume in pwMS.…”
Section: Introductionmentioning
confidence: 99%